Strategic Digital Marketing And Livestreaming Implementation For Automotive Care Sales: Implementasi Strategi Pemasaran Digital Dan Livestreaming Pada Penjualan Perawatan Otomotif - Muhammad Saddam Navaro; Alshaf Pebrianggara (Procedia of Social Sciences and Humanities, 2026)
General Background The rapid growth of internet connectivity has transformed modern commercial practices, compelling businesses to adopt online platforms for product promotion. Specific Background Tuxedo Autocare, an automotive care brand, utilizes Instagram, TikTok, and Shopee live broadcasting to reach consumers, yet experienced a recent decline in monthly revenue. Knowledge Gap While social media promotion is widely adopted, the specific operational constraints and content engagement variations that hinder consistent revenue generation in local automotive care businesses remain underexplored. Aims This study investigates the applied digital commercial strategies, identifies operational obstacles, and formulates optimization tactics for Tuxedo Autocare. Results A qualitative descriptive analysis reveals that emotional content generates the highest audience impressions on Instagram, while interactive and comedic live broadcasting significantly recovers declining revenue. However, the brand faces critical operational barriers, including inconsistent broadcasting schedules, limited content innovation, insufficient branding personnel, and a lack of dedicated communication devices. Novelty This research provides a direct evaluation of content-specific engagement metrics and real-time live commerce constraints within a local automotive care enterprise. Implications Enterprises must prioritize consistent broadcasting schedules, diversify interactive content, and allocate dedicated resources for digital management to ensure sustainable commercial growth. Highlights: Emotional content on social media generates significantly higher audience impressions than direct promotional materials. Integrating interactive dialogue and comedy during real-time broadcasting directly recovers declining commercial revenue. Inconsistent schedules and inadequate dedicated equipment severely restrict the optimization of promotional strategies. Keywords: Digital Marketing, Live Broadcasting, Automotive Care, Content Strategy, Commercial Revenue